The Politics of Italy : Governance in a Normal Country / [electronic resource] - Newell, James L. (Cambridge : Cambridge University Press, 2010)
This innovative text offers a completely fresh approach to Italian politics by placing it in its historical, institutional, social and international contexts. Students will get to grips with the theories and concepts of comparative politics and how they apply specifically to Italy, while gaining real insight into more controversial topics such as the Mafia, corruption and the striking success of Berlusconi. The textbook uses clear and simple language to critically analyze Italy's institutions, its political culture, parties and interest groups, public policy, and its place in the international system. Often regarded as an anomaly, Italy is frequently described in terms of 'crisis', 'instability' and 'alienation'. Sceptical of these conventional accounts, Newell argues that, if understood in its own terms, the Italian political system is just as effective as other established democracies. With features including text boxes and further reading suggestions, this is an unbeatable introduction to the politics of Italy.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).